Hydroxyl radical-mediated oxidative cleavage of CC bonds and further esterification reaction by heterogeneous semiconductor photocatalysis. Issue 17 (12th August 2021) - Wang, Hui; Jia, Rui; Hong, Mei; Miao, Hongyan; Ni, Bangqing; Niu, Tengfei
Abstract : A tubular carbon nitride (TCN) photocatalysis hydroxyl radical-mediated aerobic cleavage of alkenes and further sequence esterification reaction. Abstract : A hydroxyl radical-mediated aerobic cleavage of alkenes and further sequence esterification reaction for the preparation of carbonyl compounds have been developed by using tubular carbon nitride (TCN) as a general heterogeneous photocatalyst under an oxygen atmosphere with visible light irradiation. This protocol has an excellent substrate scope and gives the desired aldehydes, ketones and esters in moderate to high yields. Importantly, this metal-free procedure employed photogenerated hydroxyl radicals in situ as green oxidation active species, avoiding the present additional initiators. The reaction could be carried out under solar light irradiation and was applicable to large-scale reactions. Furthermore, the recyclable TCN catalyst could be used several times without a significant loss of activities.